GNAS, PDE4D, and PRKAR1A Mutations and GNAS Methylation Changes Are Not a Common Cause of Isolated Early-Onset Severe Obesity Among Finnish Children - Loid, Petra; Pekkinen, Minna; Reyes, Monica; Mustila, Taina; Viljakainen, Heli; Jüppner, Harald; Mäkitie, Outi (Frontiers in Pediatrics, 2020)
Context: Pseudohypoparathyroidism type Ia (PHP1A) is caused by inactivating mutations in GNAS exons 1-13, encoding the alpha-subunit of the stimulatory G protein (Gsα). Particularly PHP1A, but also other disorders involving the Gsα-cAMP-signaling pathway, have been associated with early-onset obesity. Thus, patients with mutations in the genes encoding PDE4D and PRKAR1A can also be obese. Furthermore, epigenetic GNAS changes, as in pseudohypoparathyroidism type Ib (PHP1B), can lead to excessive weight. Objective: Search for genetic variants in GNAS, PDE4D and PRKAR1A and for methylation alterations at the GNAS locus in Finnish subjects with severe obesity before age 10 years. Methods: Next generation sequencing to identify pathogenic variants in the coding exons of GNAS, PDE4D and PRKAR1A; Multiplex Ligation-dependent Probe Amplification (MLPA) and methylation-sensitive MLPA (MS-MLPA) to search for deletions in GNAS and STX16, and for epigenetic changes at the four differentially methylated regions (DMR) within GNAS. Results: Among the 88 subjects (median age 13.8 years, median body mass index Z-score +3.9), we identified one rare heterozygous missense variant of uncertain significance in the XL exon of GNAS in a single patient with isolated severe obesity. We did not identify clearly pathogenic variants in PDE4D and PRKAR1A, and no GNAS methylation changes were detected by MS-MLPA. Conclusions: Our results suggest that coding GNAS mutations or methylation changes at the GNAS DMRs, or coding mutations in PDE4D and PRKAR1A are not common causes of isolated childhood obesity in Finland.